Social entrepreneurship in sport : how sport can deliver social wellbeing - Ratten, Vanessa (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The social role of sport enterprises is being increasingly recognized at both local and global levels. Sport has the ability to influence community cohesion, physical and mental health, social inclusivity, and provides positive role models across society. More businesses in sport are incorporating these social aspects into their plans as a way of differentiating themselves from their competitors. This, in turn, has led to more social innovation in sport. Recently, there has been more emphasis on social entrepreneurship in sport due to the growing need to capture the societal impact of sport. This book explores the non-profit role sport plays in society, and demonstrates how social enterprises can both address some of the negative social outcomes of sport and support businesses as they develop their social objectives. The over-arching aim of the book is to focus on how social entrepreneurship in sport is important in developing a better global society"--
Social entrepreneurship in sport : an introduction -- Value creation and social entrepreneurship -- Processes and mechanisms for social entrepreneurship -- Entrepreneurial ecosystems in sport -- Strategies for social entrepreneurship -- Gender and social entrepreneurship in sport -- The future of social entrepreneurship in sport.
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Social aspects; Sports administration -- Social aspects; Social entrepreneurship; Well-being -- Social aspects; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Auditing; BUSINESS & ECONOMICS / Business Ethics